2013
DOI: 10.1080/14636778.2013.764069
|View full text |Cite
|
Sign up to set email alerts
|

Biodigital Publics: Personal Genomes as Digital Media Artefacts

Abstract: The recent proliferation of personal genomics and direct-to-consumer (DTC)genomics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…O'Riordan has noted how 23andMe frames its customers as publics who read and write about their genomes, whilst obfuscating how the focus on DNA constrain these practices (O'Riordan, 2013), and Kragh-Furbo and Tutton have observed how the company has turned customers' saliva into a promissory substance, which is easy to circulate in the bioeconomy (Kragh-Furbo & Tutton, 2017). I agree with the observations of these authors.…”
supporting
confidence: 40%
See 1 more Smart Citation
“…O'Riordan has noted how 23andMe frames its customers as publics who read and write about their genomes, whilst obfuscating how the focus on DNA constrain these practices (O'Riordan, 2013), and Kragh-Furbo and Tutton have observed how the company has turned customers' saliva into a promissory substance, which is easy to circulate in the bioeconomy (Kragh-Furbo & Tutton, 2017). I agree with the observations of these authors.…”
supporting
confidence: 40%
“…Critical social scientists have observed that 23andMe mobilises concepts associated with the participatory or democratic potential of digital media, such as open source, being part of a community and sharing, to legitimise collecting customers' DNA and other data to be sold for profit (Harris et al, 2016;O'Riordan, 2013;Van Dijck & Poell, 2016). The analysis of how the company mobilised the metaphor of big data illustrates how 23andMe legitimised its operation by casting genes not as a special code to be cracked by the cognoscenti but as any digital data resource to be circulated among the many.…”
Section: Discussionmentioning
confidence: 99%
“…The merging of genetic material and digital participation has been described as a new form of self-discovery and social belonging (Harris et al, 2014;O'Riordan, 2013). Technocultural elites promote the position that people need data and algorithms in order to engage in self-discovery, supplementing the body as a site of knowledge and authority by a notion of the body as knowable only through numerical and computational practices (O'Riordan, 2011, p. 300;Ruckenstein & Pantzar, 2015).…”
Section: The Inhabitable Map Of Genetic Testingmentioning
confidence: 99%
“…scholarly work that treats DTC genetic testing as part of an expanding market of commercial products and services promoting self-tracking and uses of personal data which, in turn, shape communication, social life, and identities (Harris, Wyatt, & Kelly, 2013Lomborg & Frandsen, 2016;O'Riordan, 2011O'Riordan, , 2013Ruckenstein & Pantzar, 2015). By proposing a comprehensive approach to DTC genetic testing, the aim is to explore wider opportunities for action and agency in terms of genetic knowledge than is suggested by mainstream research which focuses, for instance, on motivations for being tested, the clinical utility and validity of the test results, or their value in terms of personal risk assessment and behavior change (e.g., McGowan, Fishman, & Lambrix, 2010;Su, Howard, & Borry, 2011).…”
mentioning
confidence: 99%
“…Scholars have observed that the company frames its service using participatory rhetoric of ‘open access’, ‘community’, and ‘reading’ genomes whilst extracting ‘unpaid labour’ from its consumers by selling their data (Harris et al . ; O'Riordan ; Van Dijck and Poell ). I have analysed how 23andMe represented genes through the new metaphor of big data to strategically draw on its participatory connotations (Saukko ).This article takes these conversations forward by conceptualising the alleged participatory nature of 23andMe in the broader context of medical cosmologies and digital health.…”
Section: Methodsmentioning
confidence: 99%